D’une certaine anthropologie et de quelques anthropologues - Labrecque, Marie France (Anthropologica, 2022)
In this article, the author tries to share her vision that research is one of the social functions of anthropology. With this aim in mind, she uses the technique of the tale written in the first person while locating her own experience in a larger disciplinary setting. She first recollects the reasons and the interrogations that drove her, at the end of the 1960s, to study anthropology at Laval University, Quebec City. She then roughs out a general profile of the sociopolitical context in which training in anthropology was done at that time and at that location. Finally, she acknowledges the influences both from Marxist European and American culturalist anthropology and shows how they concretize through her research orientations to the present. All along, she tries to remain in touch with the motivations of the students who continue to adhere to anthropology because they are interested in social change.